Brain N-Acetyl Aspartate and associations with cognitive impairment in alcohol dependent patients. Issue 2 (7th February 2020) - Morley, Kirsten C.; Lagopoulos, Jim; Logge, Warren; Chitty, Kate; Moustafa, Ahmed A.; Haber, Paul S.
ABSTRACT: Introduction : Chronic alcohol consumption has been observed to be associated with a range of cognitive impairments that impact on treatment management. In this spectroscopy study, we examined the association of N-Acetyl Aspartate (NAA), a marker of neuronal integrity, and cognitive impairment in alcohol dependent patients. Method : Using in vivo proton magnetic resonance spectroscopy ( 1 H-MRS), we examined brain metabolite levels in 31 alcohol dependent individuals. 1 H-MRS from the parietal lobe were analyzed to yield absolute concentrations of NAA. Alcohol history, neurocognitive function including Clock Drawing Test (CDT), Mini Mental State Exam (MMSE), Trial Making Test (TMT) and Balloon Analogue Risk Task (BART) were also assessed. Covariates included concurrent medication, age and recent alcohol consumption. Results : There were statistically significant bivariate associations between NAA and the variables age, CDT and BART (r = −.45, P = 01; r = −.53, P = .01; r = .49, P = .02) respectively) but there were no statistically significant associations with other measures of cognitive function. Controlling for age, concurrent medication and recent alcohol consumption, multiple linear regression revealed a negative association between parietal NAA (Model: F = 6.96, R 2  = .66, P = .001) and CDT scores ( B = −.35, P = .03), a positive association with BART scores ( B = .47, P = .02). Conclusion : These results demonstrate that in alcohol dependent patients lower NAA/Cr is associated with reduced cognitive functioning and increased risk-taking.